Efektivitas Trichoderma sp. dan Gliocladium sp. sebagai Agen Biokontrol Hayati Penyakit Busuk Pelepah Daun pada Jagung - Soenartiningsih, Soenartiningsih; Djaenuddin, Nurasiah; Saenong, M. Sujak (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2014)
Sheath blight is an important disease in corn. The disease could cause significant yield loss when infection occurs on susceptible varieties. Disease control using the microorganism antagonist is an alternative for disease management. Research was carried out in a laboratory, greenhouse and field from 2010 to 2012. The research objective was to compare several biological agents for controlling sheath blight disease on corn. In vitro laboratory tests identified that out of sixteen isolates of microorganisms, only 3 isolates which had the potency to suppress the pathogen of sheath blight over 50%, namely TT1; TM; and GM. Conidia development among the three isolates of microorganism the highest was by TT1. In the greenhouse, three isolates of microorganisms showed potential of decreasing sheath blight disease up to 70%. The Gliocladium isolates decreases the disease by 53%. Research results from the field indicated the antagonist had decreased sheath blight disease by 67%. Isolates of Trichoderma and Gliocladium fungus could reduce the yield loss by 23% by suppressing the infection of sheath blight disease.